2015
DOI: 10.1073/pnas.1502956112
|View full text |Cite
|
Sign up to set email alerts
|

Biotic interactions mediate soil microbial feedbacks to climate change

Abstract: Decomposition of organic material by soil microbes generates an annual global release of 50–75 Pg carbon to the atmosphere, ∼7.5–9 times that of anthropogenic emissions worldwide. This process is sensitive to global change factors, which can drive carbon cycle–climate feedbacks with the potential to enhance atmospheric warming. Although the effects of interacting global change factors on soil microbial activity have been a widespread ecological focus, the regulatory effects of interspecific interactions are ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 209 publications
(146 citation statements)
references
References 36 publications
5
130
2
Order By: Relevance
“…Moreover, the response of soil respiration to temperature is not consistent across all temperature ranges, because the temperature sensitivity of respiration typically decreases under warmer conditions (21,22). As a result, the interaction between soil respiration and climate warming remains one of the greatest sources of uncertainty in climate projections, despite being an important boundary condition in current Earth system models (ESMs) (4,23,24).…”
Section: Significancementioning
confidence: 99%
“…Moreover, the response of soil respiration to temperature is not consistent across all temperature ranges, because the temperature sensitivity of respiration typically decreases under warmer conditions (21,22). As a result, the interaction between soil respiration and climate warming remains one of the greatest sources of uncertainty in climate projections, despite being an important boundary condition in current Earth system models (ESMs) (4,23,24).…”
Section: Significancementioning
confidence: 99%
“…Last, basidiomycete fungi comprise an important functional guild from a carbon cycle perspective, being the dominant decomposers of recalcitrant organic material in forested ecosystems (26)(27)(28)(29). Understanding how and when diversity affects function in basidiomycete communities therefore has important secondary implications for terrestrial carbon storage (30).…”
Section: Ecologymentioning
confidence: 99%
“…Recent research has found that plant diversity may play a more important role than temperature in determining the communities of microbes involved in carbon, nitrogen and phosphorous cycles (Steinauer et al, 2015), and that the expected increase in soil carbon emissions arising from higher temperatures may be mediated by consumption of fungi by soil invertebrates (Crowther et al, 2015). These findings highlight the importance of considering biotic and abiotic processes together.…”
Section: Modelling Nutrient Cycles and Ghg Balancesmentioning
confidence: 99%